A study of factors leading to post-operative leaks following bowel anastomosis - Srinivas, L.; Venkatesh, B.; Ahmad, Samir (International Surgery Journal, 2018)
Background: Intestinal anastomosis is one of the most commonly performed procedures, especially in the emergency setting and is also in the elective setting when resection is carried out for benign or malignant lesion of the gastrointestinal tract. Anastomotic leakage is a potentially disastrous complication, which can lead to sepsis and abdominal catastrophe. The aim of the study is to determine factors leading to post-operative leaks in gastrointestinal surgeries involving different kinds of anastomosis and to determine the role of parameters such as pre-operative hemoglobin, serum albumin, indication for surgery, degree of contamination, type of anastomosis, technical variations and postoperative management in anastomotic leaks. We also aim to determine the morbidity and mortality variation and to study the various presentations of anastomotic leak in the patient group as well. Methods: A prospective study was conducted from December 2015 till the end of august 2017 at Prathima Institute of Medical Sciences, Karimnagar. All patients undergoing gastrointestinal anastomosis electively and as an emergency procedure were included in this study. The total number of cases studied is 60. Results: Out of the 60 cases in this study, 49 cases were done electively, and 11 cases were done on an emergency basis. Anastomotic leaks occurred most in emergency cases (27.27%). Among 5 patients, (71.42%) leaks were managed conservatively and rest required intervention. There was increased death rate in patients with leak. Leaks occurred maximum in jejunoileal anastomosis. Most common organ involved was esophagus (28.57%). Conclusions: Anastomotic leaks are a common complication following all types of gastrointestinal anastomosis. It is believed, hypoalbuminemia hinders anastomotic healing. Surgeries indicated in emergency situation carried increased risk of operative leaks in post-operative period.